Detecting Analysis Fraud That Occurs In The Financial Statements Of Pharmaceutical Companies In A Retur Study (Journal of Pharmaceutical Negative Results, 2023)
Pharmaceutical companies are one of the largest companies in the country that are trusted by the public engaged in medicines . One of the ways to see its performance is to look at the condition of the company. but inside In practice , pharmaceutical financial reports have experienced financial problems and sales of health products. This study discusses detecting Fraud that occurred on Financial Statements in pharmaceutical companies . The research method uses qualitative methods. The method of collecting data is by studying repetition, namely by searching for articles, notes, letters, reading books, studying, digesting, and analyzing, as well as journals and the results of previous research related to D ecthesis Fraud that occurs on Financial Statements in pharmaceutical companies , then displayed and published in a theoretical framework. The results of the research conducted, it turns out that there has been a misstatement in the presentation of financial statements and problems selling health goods products to the public. This will have an impact on the presentation of financial statements, because there is an element of fraud that occurs.